2004
DOI: 10.1089/104303404322959551
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Adenoviral and Adeno-Associated Viral Vectors for Pancreatic Gene DeliveryIn Vivo

Abstract: Although effective gene therapy vectors have been developed for organ systems such as the liver, an effective delivery vector to the pancreas in vivo has remained elusive. Of the currently available viral vectors, adenovirus and adeno-associated virus (AAV) are two of the most efficient at transducing nondividing cells. We have constructed recombinant adenovirus (AdVLacZ), adeno-associated virus serotype 2 (AAV2LacZ), and pseudotyped adeno-associated virus serotype 5 and 8 (AAV5LacZ, AAV8LacZ) carrying the Lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
102
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 30 publications
(23 reference statements)
6
102
0
Order By: Relevance
“…Thus far, no effective and stable in vivo gene transfer to the islets has been achieved using a variety of gene transfer systems. Recent studies showed that the adenovirus has been the best available vector system, which rendered limited and transient gene transfer to the islets in vivo, but suffered from host immune responses and vector cytotoxicity (17)(18)(19). Direct intrapancreas injection of adeno-associated virus (AAV) vectors containing conventional single-stranded vector DNA genomes also only achieved very limited islet gene transfer (19).…”
mentioning
confidence: 99%
“…Thus far, no effective and stable in vivo gene transfer to the islets has been achieved using a variety of gene transfer systems. Recent studies showed that the adenovirus has been the best available vector system, which rendered limited and transient gene transfer to the islets in vivo, but suffered from host immune responses and vector cytotoxicity (17)(18)(19). Direct intrapancreas injection of adeno-associated virus (AAV) vectors containing conventional single-stranded vector DNA genomes also only achieved very limited islet gene transfer (19).…”
mentioning
confidence: 99%
“…However, their utility for targeting pancreatic islets in living animals has proved to be limited. Thus, direct injection of recombinant adenovirus or adeno-associated virus into the pancreas results in variable expression of reporter genes in exocrine cells, with negligible expression in pancreatic islets (5). An alternative approach, jugular vein infusion of a ␤-galactosidase adenovirus into rats during surgical clamping of the hepatic and portal circulation, resulted in ␤-galactosidase expression in 70% of islets.…”
mentioning
confidence: 99%
“…Adenoviruses are also capable of infecting both replicating and non-replicating cells, but do not integrate their DNA into the host cell genome, and can elicit a strong immune response in animals (Wang et al, 2004). Adenovirus-mediated delivery of Cas9 has been used to achieve in vivo genome editing in mouse lungs (Maddalo et al, 2014) and livers Ding et al, 2014;Wang et al, 2015a).…”
Section: Delivery Of Genome-editing and Epigenome-editing Agentsmentioning
confidence: 99%